Moderating effect of green technology adoption on stakeholder influence and environmental sustainability practices in small and medium textile enterprises in Bangladesh - Hossain, Mohammad Imtiaz (2021)
Businesses are increasingly becoming conscious of the environmental aspects of their operations due to increasing consumers awareness with regards to environmental impact of their consumption choices. The willingness to reduce their ecological footprint has created new market opportunities as well as stakeholders’ pressure. Consequently, green initiatives are evolving into a crucial part of strategic planning in organizations, including small and medium enterprises (SMEs). Although SMEs differ from large companies not only in terms of their size but also other characteristics, their combined impact on environment is significantly higher than big companies. Green technology adoption (GTA) with the coordinated effort of stakeholders can minimize this negative impact. Thus, the objective of this research is to determine the relationship between stakeholder influence (SI) and environmental sustainability practices (ESP), as well as examining the moderating effect of the perception of green technology adoption (GTA) in Bangladesh Textile SMEs in Dhaka, Bangladesh. The current research follows a post positivist, quantitative, deductive, confirmatory, and cross-sectional approach for the study. A structured questionnaire is used in this research to obtain primary data from 140 textile SMEs. The owners and managers are targeted as they have the supreme power and information about installing any strategic change. SPSS23 and Smart-PLS 3.2.9 are used for data analysis. Analysis of the findings showed that buyers’ pressure (BP), community engagement (CE), employees’ involvement (EI), government regulation (GR), management support (MS) have positive relationship with ESP except suppliers’ pressure (SP). The perception on GTA only moderate suppliers’ pressure (SP). The weak integration of stakeholders with the Bangladeshi textile SMEs and low level of technological awareness and adoption, support these findings. This study serves as a pioneer effort to investigate the effect of SI on ESP with the moderation of perception on GTA in Bangladesh textile SMEs. The findings of this research provide new directions for future research and several crucial implications to the other manufacturing SMEs and policymakers.